WARRANTLESS SEARCHES AND AWARDS FOR DAMAGES IN LIGHT OF THE JUDGMENT IN Shashape v The Minister of Police Case No.: 1566/2018 - Delano Cole van der Linde (Obiter, 2021)
The law of criminal procedure is “double functional” in that it not only dictates the proper procedure for the execution of police functions but also serves as a ground of justification in substantive law against otherwise unlawful conduct. Nevertheless, personal liberties, even in the pursuit of justice in a country overrun by crime, cannot be sacrificed indiscriminately simply to further the diligent investigation of crime. An example of personal liberties being sacrificed in favour of the pursuit of justice is the search and seizure of private spaces of individuals. Search and seizure may be effected both with and without a warrant and is regulated by the Criminal Procedure Act 51 of 1977 (CPA). However, where a police official acts outside of this legislative matrix, his or her conduct is not regarded as lawful; he or she may not rely on official capacity as a ground of justification against an (unlawful) search. In such instances, the Minister of Police may be vicariously liable in delict owing to the unlawful conduct of police officials. Such cases are relatively rare. This contribution will focus on two specific aspects – namely, search and seizure conducted without a warrant, and subsequent awards for damages based on unlawful, warrantless searches. The recent judgment in Shashape v The Minister of Police (WHC (unreported) 2020-04-30 Case no 1566/2018 (Shashape)) is discussed against this backdrop.